Green coffee extract enhances oxidative stress resistance and delays aging in Caenorhabditis elegans. (June 2017) - Amigoni, Loredana; Stuknytė, Milda; Ciaramelli, Carlotta; Magoni, Chiara; Bruni, Ilaria; De Noni, Ivano; Airoldi, Cristina; Regonesi, Maria Elena; Palmioli, Alessandro
Highlights: Green coffee extract composition was verified by NMR and UPLC/ESI-HRMS analyses. The antioxidant activity of the extract was assessed. Green coffee extract displayed an anti-aging effects in Caenorhabditis elegans. The extract showed a major effect respect to pure 5-CQA. Abstract: Nutritional factors play a pivotal role for healthy aging and longevity. This is related to the antioxidant properties of the molecules present in some foods. Due to the high content of polyphenols, Green Coffee Extract (GCE) is a powerful antioxidant. Nevertheless, little is known about its effect on aging. We demonstrated the benefic effects of GCE on stress resistance, fertility and adult mean lifespan using Caenorhabditis elegans as a model. The mean and maximum lifespan of worms treated with GCE increased significantly in a dose-dependent manner, and animals pre-treated were more resistant to oxidative stress. NMR and UPLC/ESI-HRMS analyses of GCE confirmed a significant content of chlorogenic acids, being 5- O -caffeoylquinic acid (5-CQA) the most abundant isomer. The major activity demonstrated by GCE in comparison to the pure 5-CQA on C. elegans phenotypes clearly demonstrated the importance of the employment of a natural extract to develop functional foods and supplements.